Birmingham Royal Orthopaedic Hospital (BROH) Femoral Offset—An Ancillary Measure of Adult Dysplasia of the Hip - Iyengar, Karthikeyan P.; Fitzpatrick, John D.; Michalos, Michail; McBryde, Callum; Politis, Angelos; Bache, Ed; Wall, Peter; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2023)
Introduction Adult dysplasia of the hip (ADH) is a disorder of abnormal development of the hip joint resulting in a shallow acetabulum and uncovering of the femoral head. Several radiological measurements such as the Tönnis angle (acetabular index), lateral center edge angle of Wiberg, and cross-sectional imaging parameters exist to calculate hip dysplasia.Aims The aim of this article was to describe a new ancillary linear measure of ADH on cross-sectional imaging, the Birmingham Royal Orthopaedic Hospital (BROH) Femoral offset.Patients and Methods Anteroposterior radiographs of the pelvis and computed tomography imaging of 100 consecutive patients with suspected hip dysplasia were reviewed. Demographic details and clinical indications were recorded. Tönnis angle was utilized to measure hip slope on radiographs and the BROH femoral offset was calculated for each patient. Student's t-test and one-way analysis of variance (ANOVA) were performed. Intraclass correlation coefficient analysis was evaluated to assess the reliability between observers.Results There was a total of 100 patients (128 hips) included in the study (60 with normal Tönnis angle, 53 had dysplasia, and 15 had decreased Tönnis angle). The average BROH femoral offset in the dysplastic cohort was increased in comparison to the normal cohort with a statistically significant p-Value of 0.0001. The p-value was 0.00031 on ANOVA. The BROH femoral offset calculation revealed good intra- and interobserver reliability of 0.9 and 0.9, respectively.Conclusion The BROH femoral offset can be an additional index for measuring ADH that is easier to calculate, and reproducible with good intra- and inter-observer reliability on cross-sectional imaging.
Keywords: adult hip dysplasia; acetabular dysplasia; radiography; pelvic radiograph; Tönnis angle; computed tomography